Large-eddy Simulation of the Planetary Boundary Layer under Baroclinic Conditions During Sunset Turbulence - Rizza, Umberto; Degrazia, Gervásio A.; Acevedo, Otávio C.; Goulart, Antonio G. (Ciência e Natura, 2011)
.